Gold Dust - Al-koni, Ibrahim; Cola, Elliot (Cairo The American university in cairo press, 2020)
The very essence of this is life. our relationship with life is at the core of our state of being. this relathionships defines all existential and experiental relationships we have with others
Keywords: Arabic Fiction; Arabic Liteature